The novel in vitro reanimation of isolated human and large mammalian heart-lung blocs. Issue 1 (December 2016) - Goff, Ryan; Howard, Brian; Quallich, Stephen; Iles, Tinen; Iaizzo, Paul
Abstract Background In vitro isolated heart preparations are valuable tools for the study of cardiac anatomy and physiology, as well as for preclinical device testing. Such preparations afford investigators a high level of hemodynamic control, independent of host or systemic interactions. Here we hypothesize that recovered human and swine heart-lung blocs can be reanimated using a clear perfusate and elicit viable cardiodynamic and pulmonic function. Further, this approach will facilitate multimodal imaging, which is particularly valuable for the study of both functional anatomy and device-tissue interactions. Five human and 18 swine heart-lung preparations were procured using techniques analogous to those for cardiac transplant. Specimens were then rewarmed and reperfused using modifications of a closed circuit, isolated, beating and ventilated heart-lung preparation. Positive pressure mechanical ventilation was also employed, and epicardial defibrillation was applied to elicit native cardiac sinus rhythm. Videoscopy, fluoroscopy, ultrasound, and infrared imaging were performed for anatomical and experimental study. Results Systolic and diastolic left ventricular pressures observed for human and swine specimens were 68/2 ± 11/7 and 74/3 ± 17/5 mmHg, respectively, with associated native heart rates of 80 ± 7 and 96 ± 16 beats per minute. High-resolution imaging within functioning human pulmonary vasculature was obtained among other anatomies of interest. Note that one human specimen elicited poor cardiac performance post defibrillation. Conclusions We report the first dynamic videoscopic images of the pulmonary vasculature during viable cardiopulmonary function in isolated reanimated heart-lung blocs. This experimental approach provides unique in vitro opportunities for the study of novel medical therapeutics applied to large mammalian, including human, heart-lung specimens.